A Study to Evaluate Relative Bioavailability, Food Effect, and Pharmacodynamics of Tropifexor, a Farnesoid X Receptor Agonist, in Healthy Participants. Issue 2 (10th December 2022) - Stringer, Rowan; Chen, Jin; Shah, Bharti; Gu, Jessie; Zhang, Yiming; Prince, William; Klickstein, Lloyd B.; Woessner, Ralph
Abstract: This open‐label, randomized, 3‐treatment, 3‐period, 6‐sequence, crossover study in healthy subjects compared the pharmacokinetic and pharmacodynamic properties of a lipid‐based (soft gelatin capsule) prototype final market image (pFMI) formulation of tropifexor (90‐µg) to its clinical service form (CSF) and assessed the food effect for the pFMI formulation. In the fasted state, drug exposure was higher for the pFMI. The geometric mean ratios for pFMI versus CSF of peak concentration and area under the concentration–time curve were 2.0 and 1.5, respectively. No food effect was apparent for the pFMI formulation, and the geometric mean ratios for pFMI fed versus pFMI fasted of peak concentration and area under concentration–time curve were 1.0 and 1.0 respectively. Despite having lower systemic exposure, the CSF formulation provided a higher pharmacological response for the gut biomarker fibroblast growth factor 19. Under fasted conditions, fibroblast growth factor 19 maximum change from baseline serum concentration after drug administration and area under the change from baseline serum concentration–time curve from time 0 to 24 hours were 36% for CSF and 12% for FMI. For a second biomarker, serum 7‐alpha hydroxy‐4‐cholest‐3‐one, the pharmacological activity was comparable between CSF (fasted) and pFMI (both fasted and fed states). The pFMI offers advantages over the CSF in terms of insensitivity to food effect, lower intersubject variability, and overcoming solubility limitations.